Changes in volatile organic compounds (VOCs) content in resistant and non-resistant forest trees in response to bark beetle attack - Petr Soudek; Jan Rezek; Kateřina Moťková; Šárka Petrová; Pavlína Máchová; Adam Véle; Martin Fulín; Petr Hošek (Journal of Forest Science)
The response of forest trees to bark beetle attack involves substantial changes in terpene content, which varies between resistant and non-resistant species. Terpenes serve as crucial chemical defences against pests, and their production can be influenced by prior attack history, water stress, and biotic interactions. Moreover, the effectiveness of terpenes in resisting bark beetle attack is influenced by their chemical composition. Different tree species produce different types and amounts of terpenes that can affect their overall resistance levels. In conifers, acyclic and cyclic monoterpenes and sesquiterpenes were significantly present in all samples. Acyclic monoterpenes, ketones, aldehydes, monocarboxylic acids and their esters, and aromatic and cyclic compounds have been identified in beech. A statistically significant decrease of compounds in infested trees was determined in pine (cis-β-ocimene, neo-allo-ocimene, terpinene-4-ol, and δ-cadinene), and fir (acetophenone, benzonitrile, phenol, and zonarene). In addition, increased benzaldehyde production was observed. However, in infested beech trees, only increased production of some aliphatic and aromatic compounds (2-butanone and 3,5-octadien-2-one, 2-methyl-4-pentenal and 2,4-hexadienal, octanoic acid, nonanoic acid, 3,4-dimethyl-2,5-furandione, acetophenone, benzeneacetaldehyde, 2-ethyl-1H-pyrrole, β-ionone-5,6-epoxide, β-cyclocitral, and geranyl acetone) was found. We investigated the changes in the terpene composition of surviving trees in bark beetle-infested stands of beech (Fagus sylvatica), pine (Pinus sylvestris), and fir (Abies alba). Our data showed that the distribution of different groups of volatile compounds varied according to the tree species.